Y llegó Nociones (de Samuel Gili Gaya) - Polo, José (Revista de Filología Románica, 2008)
In this article, the last stage of a minor trilogy through which the way for an extensive work on the same area is paved, man attracts attention to a brief elementary treatise on historical grammar (from Gili Gaya), successful booklet if we take the chronological circunstances into account.